FEASIBILITY OF A HOME-BASED CARDIAC REHABILITATION PROGRAM AMONG ADULTS WITH CARDIOVASCULAR DISEASE: A PILOT STUDY - Tim Bilbrey, EP, MBA (Elsevier, 2024)
Therapeutic Area: Rehabilitation Background: Home-based cardiac rehabilitation (HBCR) has the potential to improve access to cardiac rehabilitation for patients recovering from acute cardiovascular disease (CVD). This study aims to assess the feasibility and initial impact of a technology-enabled HBCR program delivered by a multidisciplinary team to patients with CVD. Methods: This prospective, single-arm study used a within-subject design. We recruited patients (age 40+) from the community with a CR-eligible diagnosis (stable angina pectoris, myocardial infarction, heart failure, etc.). All eligible and enrolled patients referred to the RecoveryPlus.Health (RPH) remote CR clinic in Roanoke, TX between May and August of 2023 were included. The care team provided guideline-concordant CR services to study participants via two modalities: 1) synchronous telehealth exercise training via video conferencing; and 2) asynchronous mHealth virtual coaching app. Baseline survey and electronic health record (EHR) data were used to extract sociodemographic and clinical data. Feasibility was measured by program completion rate and CR service use. Preliminary efficacy was measured by changes in 6-minute walk test (6MWT), resting heart rate, and quality of life (SF-12) before and after the 12-week program. Paired t tests were used to examine the changes in the outcome variables post intervention. Results: A total of 75 patients consented and were enrolled in the study. The average age was 64.2 (SD=10.3, Range: 45-85) and 50.7% were female. The most frequent referring diagnosis was heart failure (49.3%). 62 (82.7%) participants completed the 12-week study. Among those who completed the study, all patients attended the telehealth sessions and 60 (95.2%) used the mHealth App. Post intervention, participants on average improved their 6MWT by 40.0 meters (ES=0.632, 95% CI: 0.356 to 0.877), indicating better cardiorespiratory endurance. The physical and mental summary scores were also improved by 2.7 (ES=0.413) and 2.2 (ES=0.244), respectively. There were no differences in resting heart rate and no serious program-related adverse events were reported. Conclusions: The pilot data showed that the HBCR program was feasible in delivering remote CR care to patients at home. The promising preliminary results suggest that a randomized controlled efficacy trial is warranted.